Kaiyrmanova G.K., Darmenkulova Zh.B., Ernazarova A.K. Diversity of micro organisms petroleum reservoir waters: Al-Farabi Kazakh National University, Kazakhstan, Almaty (Eurasian Journal of Ecology, 2018)
In-process gave there are quantitative and quality microbiologicaldescription of standards of petroleum waters of deposits of «Kulsari» and«Zhetibay». It is discovered that common amount of microorganisms ofpetroleum waters of deposit of «Kulsari» higher what deposits «Zhetibay»and 25,1х106 makes ; 1,8х106/ml, accordingly. It is educed, that in petroleum waters «Zhetibay» there are spore-formers, micromitcety, pseudomonads, bacilli and enterobacters, while, pseudomonads are not educedin the standard of petroleum waters of «Kulsari». During works, from thestandards of petroleum waters of deposits of «Kulsari» and «Zhetibay» 15is distinguished and 18 cultures of microorganisms, accordingly. To thedistinguished cultures of microorganisms of gave мicro- and micromorphological description. There are cultures of aborigines of microorganismsof КМ- 2 on macromorphological researches, КМA – 2, КG- 1, ZHМ – 1,ЖМ- 2, ЖG- 1, ЖG- 3, ЖС- 1, NКК- 2, NКZH- 1 are round colonies lightyellow, brilliant, with a smooth surface and even edges. During an experiment 33 cultures of microorganisms were distinguished from the standardsof petroleum waters Zhetibay and Kulsari. In practical experience macromorphological description of microorganisms was given abstracted fromthe standards of petroleum waters of deposit of «Кulsari» and «Zhetibay».Key words: nefteplast waters, mikromitcety, spore-formers, microbalcultures, bacilli, entorobacters